От новой драмы к драме постмодернизма - Бондаренко, Л.В. (Культура народов Причерноморья, 2003)
Postmodernism is the term used either for the time period or for the philosophic and literary trend Unlike modern drama, postmodern, one is not meant in controversy with tradition (Seneca, Shakespear, Marlow). It is a fresh view on eternal issues. Drama of postmodern times would sooner manifest its novelty in form than in ideas, giving a new life to the classics. It allows pluralism of ideas and variety of realities. Succeeding modern drama it draws on both classical and the new one (B.Shaw). Modern drama worked out the way for the postmodern one by breaking with tradition by which inducing return to the classical sources.